Brucellosis in Immunocompromised Hosts - KA Al-Anazi; AM Al-Jasser (Archives of Organ Transplantation - Peertechz Publications, 2016)
Recently, the incidence of brucellosis in immunocompromised patients has increased due to the parallel increase in the number of individuals with low immunity such as cancer patients and recipients of stem cell and solid organ transplantation. Additionally, the immunity of pregnant females is reduced and this makes them more susceptible to infections by various microorganisms including Brucella species. In immunocompromised hosts, the clinical manifestations of brucellosis are very variable and complicated infections are prone to develop. Despite the recent progress in the diagnostics and therapeutics of brucellosis, interpretation of certain diagnostic tests in immunocompromised patients is occasionally difficult and treatment of the disease in this category of patients is also difficult due not only to adverse effects of the medications employed in the treatment of brucellosis but also to the interactions between antimicrobial therapies and immunosuppressive medications.